Epicutaneous immune modulation with Bet v 1 plus R848 suppresses allergic asthma in a murine model. Issue 3 (13th December 2013) - Siebeneicher, S.; Reuter, S.; Krause, M.; Wangorsch, A.; Maxeiner, J.; Wolfheimer, S.; Schülke, S.; Naito, S.; Heinz, A.; Taube, C.; Vieths, S.; Scheurer, S.; et al.
Abstract Background Combining allergen(s) with an adjuvant is a strategy to improve the efficacy and safety of allergen‐specific immunotherapy. Here, we aimed at investigating the adjuvant effects of polyadenylic–polyuridylic acid (poly(A:U)), a TLR3 agonist, and R848 (resiquimod), a TLR7 agonist, in epicutaneous immunotherapy with Bet v 1, the major birch pollen allergen, to intervene in birch pollen allergy. Methods and Results BALB/c mice received epicutaneous immunization (EPI) with recombinant Bet v 1 (rBet v 1) alone, or plus poly(A:U), or R848 on their depilated back using patches. Among the groups, EPI with rBet v 1 and R848 induced detectable levels of IFN‐γ‐producing CD4+ T cells in lymph nodes and Bet v 1‐specific IgG2a antibodies in the sera of mice. Before or after EPI, mice were sensitized with rBet v 1 plus aluminium hydroxide adjuvant and intranasally challenged with birch pollen extract. Prophylactic EPI with rBet v 1 plus R848 inhibited the production of biologically active Bet v 1‐specific IgE antibodies in sensitization. Prophylactic and therapeutic EPI with rBet v 1 plus R848 suppressed lung inflammation upon challenges. Remarkably, only rBet v 1 plus R848 reduced the development of enhanced pause (PenH), a substituted parameter for airway hyper‐reactivity, in challenged mice. In contrast to R848, poly(A:U) did not present adjuvant effect on the suppression of asthmatic features. Conclusion Epicutaneous immunization with rBet v 1 plus R848 induced predominant Bet v 1‐specific Th1 responses and efficiently suppressed asthmatic features elicited by birch pollen. R848 could be a promising adjuvant in epicutaneous immunotherapy for birch pollen‐induced allergic asthma.